Kebijakan Program Pembiasaan Sekolah dalam Membentuk Karakter Disiplin di SMP Negeri - Giantomi Muhammad; Qiqi Yulianti Zakiah; Supiana Supiana (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
Usually the implementation of habituation programs in schools is carried out outside the main activities in the classroom. The policies taken by each school are different. In general, the habituation is devoted to the formation of the character of students, especially the character of discipline. The purpose of this habituation is so that students become accustomed and disciplined in carrying out positive activities and have an impact on their personality until adulthood. The purpose of this study was to determine the policy of the school habituation program in shaping the character of discipline in SMP Negeri 40 Bandung. This is a qualitative research that uses a phenomenological approach and a case study. After doing research, it is known that the policy of habituation program implemented at SMP Negeri 40 Bandung includes habituation of literacy, Ḍuḥā prayer, tadārus Al-Qur’ān, morning exercise, weekly community service and leardership. These activities have an impact on the personality of students. Students become more disciplined, both in the school environment and in the community. Therefore, SMP Negeri 40 Bandung is designated as an Adiwiyata School at the Bandung City level which implements school policy programs that lead to the formation of the character of students.